TARJETAS DE CRÉDITO EN AUMENTO: SOBREENDEUDAMIENTO, ALTO RIESGO ¿LA REGULACIÓN? - Mauricio Pachas, Pablo Willins (2011)
In recent years in Peru, the financing for consumption through the use of credit cards(TC) has been on the rise, allowing many individuals or families, the easy access to bank credit, which is good because immediately increases the availability for purchases of goods and services or to cash available. But on the other hand increases the financial burden, jeopardizing future income, not only for new loans but the high rate of interest that has been applied this credit. This consumer credit by using CC have accessed by more than 2 million people since May this year, banks and financial have issued 7,091.523 of CC, which amount used reaches the balance of S/.15, 208 million. The increase in CC is related to the growth of gross domestic product (GDP), which has in turn, is driving the consumption and domestic demand, resulting in increase in personal income and greater access to credit markets and loans in the financial system, behavior that is equally significant as productive to promote the modernization of the country Although, it is economically favorable to stimulate consumption and to contribute to the growth, but financially for the individuals and families, it is worrying the debt overhang and the high cost of consumer credit, given the current situation characterized by the “International Crisis” that has been generating increasing fears, as the high unemployment in European and the internal risks as the conflicts unresolved. Therefore, a reasonable uncertainty is established and an active action turns out to be necessary on behalf of the Regulation.